2019
DOI: 10.20338/bjmb.v13i2.131
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Executive Functions Within High-Level Youth Soccer Players

Abstract: Background: When measuring executive functions (EF), it is common for athletes to be assessed on their ability to detect and process explicit sources of information. Yet not all of the information is perceived explicitly in an environment. Aim: This study aimed to include a new assessment that measures the impact of implicitly perceived congruent and incongruent visual precues on response times. Method: Seventy-four male soccer players: U12 (n=15), U13 (n=17), U17 (n=21) and U19 (n=21) representing a German 1s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
3
13
0
3
Order By: Relevance
“…The studies were also divided into age categories (8–9 years, 10–11 years and 12–13 years) and it was observed that with age, the times obtained in psychomotor tests are shorter. Similar conclusions were obtained during the studies conducted by Beavan et al [ 40 ] where the reaction time of young footballers was related to age. The improvement of complex reaction time with age in young footballers was confirmed in the study of Hirose et al [ 42 ] where the complex reaction time decreased to the age of 14.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The studies were also divided into age categories (8–9 years, 10–11 years and 12–13 years) and it was observed that with age, the times obtained in psychomotor tests are shorter. Similar conclusions were obtained during the studies conducted by Beavan et al [ 40 ] where the reaction time of young footballers was related to age. The improvement of complex reaction time with age in young footballers was confirmed in the study of Hirose et al [ 42 ] where the complex reaction time decreased to the age of 14.…”
Section: Discussionsupporting
confidence: 91%
“…The measurement of the response time was also performed on young players of the German 1st league who were divided into age categories U12, U13, U17 and U19. The study shows that with age reaction time improves [ 40 ]. While Penna et al [ 41 ] showed that reaction speed did not depend on the time of birth in the group of young footballers under the age of 13.…”
Section: Introductionmentioning
confidence: 99%
“…However, caution should be taken in this approach as it may under-power the changes for each test. A more complex method that this club developed is an "EF sum score, " which combines all results into one total value (Beavan et al, 2019). Figure 1 displays the practicality of the sum score to provide a smoother translation of the relevant results to the intended audience (Buchheit, 2017).…”
Section: Communicating the Resultsmentioning
confidence: 99%
“…For example, Huijgen, Elferink-Gemser, Post, and Visscher (2010) highlighted there were no improvements from ages 16 to 19 in dribbling and sprinting, which the authors attributed to the end of puberty. Furthermore, Beavan et al (2019) revealed in a battery of cognitive function tests (e.g., Vienna Test System, which measures inhibition and cognitive flexibility) that there were no differences between U19 and U17 age groups. At this stage, further research is needed to explore whether there are peak developmental phases for cognitive factors such as decision-making.…”
Section: Discussionmentioning
confidence: 97%